Del Indian New Deal al indigenismo interamericano: Moisés Sáenz y John Collier - David Robichaux (Cahiers des Amériques Latines)
In the 1920s, the new Mexican revolutionary state adopted for its mainly Indian rural population educational policies influenced by reformist educators such as John Dewey. These policies were not only the seedbed of what would later be the country’s indigenist policy, but also drew attention in the United States. This article highlights the influence exercised by Moisés Sáenz, one of the architects of Mexico’s rural education policies, on John Collier in drawing up the Indian New Deal in the United States in the early 1930s. From their first meeting they discussed the idea of an international organization devoted to the wellbeing of the indigenous peoples of the Americas. Thanks to their efforts, in 1940 the Patzcuaro conference met and the following year the Inter-American Indian Institute was established. The article analyzes those aspects of the biographies of Collier and Sáenz that favored their relationship and how Sáenz came to be identified with a policy considered to be in the vanguard in U.S. circles. It concludes with a proposal to explain the subsequent distancing between the two and the appointment of Manuel Gamio to the post of director of the III.